Space-Based Ground Penetrating Radar Imaging of a Possible Underground Structure at Hawara - Carlotto, Mark J. (Journal of Scientific Exploration, 2025)
Space-based ground penetrating synthetic aperture radar (SAR) imaging of what could be an enormous underground structure at Hawara, possibly the below-ground portion of the Labyrinth first described by Herodotus in the fifth century BCE is presented. Cross-sensor analysis of co-registered radar and optical imagery reveals uncorrelated SAR returns on both sides of the Abdul Wahbi canal south of the Pyramid of Amenemhet III that could be the remains of an ancient settlement built from and over the Labyrinth, which was uncovered when the canal was built, as well as evidence of the Labyrinth itself.